Pengaruh Financial Technology Terhadap Kinerja UMKM Kecamatan Alang-Alang Lebar Dengan E-Commerce Sebagai Variabel Moderasi - Zikrillah, Muhammad; Sartika, Dewi (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2024)
This research aims to analyze the influence of Financial Technology (Fintech) on the performance of MSMEs with E-Commerce as a Moderating Variable. This study examines the impact of Fintech on MSMEs in Alang-Alang Lebar District, using quantitative methods to collect questionnaires. The test utilized a purposive sampling strategy to select 100 MSME actors who had previously used digital payment systems, utilizing surveys and the t-statistic, ensuring the validity of freely dispersed data without large sample sizes or normal distribution assumptions. Data were analyzed using statistical techniques to evaluate the relationships between Fintech adoption, MSME performance, and the moderating effect of E-Commerce. The results indicate that Fintech significantly influences MSME performance, as evidenced by a statistical T value of 15.772 at a significance level of 5%. The P value of 0.000, which is less than 0.05, supports this conclusion, demonstrating that Fintech adoption enhances MSME efficiency, financial management, and operational productivity. However, when testing the moderating effect of E-Commerce on the relationship between Fintech and MSME performance, the findings reveal an insignificant effect. The statistical T value of 0.909, smaller than the threshold of 1.96, and a P value of 0.363, greater than 0.05, indicate that E-Commerce does not strengthen or significantly alter the relationship between Fintech and MSME performance. The research explores the impact of Fintech adoption on MSME growth, highlighting the limited role of E-Commerce, offering valuable insights for optimizing business performance and competitiveness.